When Laws Fail: Uganda’s Anti-Corruption Frameworks and Governance Challenges During COVID-19 - Mesharch Katusiimeh; Sabiti Makara; Natal Ayiga; Abel Mucunguzi; Francis Akena; Robert B. Kakuru; Jacqueline Akello (Goodwood Publishing, 2026)
Purpose: The COVID-19 pandemic created conditions that heightened corruption risks worldwide. This was especially so in countries with fragile governance systems. Uganda, despite possessing a comprehensive set of anti-corruption laws and institutions, was widely accused of misuse of funds and resources during its pandemic response. This study assesses the effectiveness of Uganda’s legal frameworks in combating corruption under these emergency conditions. Methods: Using a qualitative research design, data were collected through 30 semi-structured interviews and 21 focus group discussions in Mbarara City, Mbarara District and Rukungiri District. This was complemented by reports from the Inspectorate of Government, the Public Procurement and Disposal of Public Assets Authority and the Auditor General. Thematic analysis revealed widespread corruption. Results: The results show that corruption during Uganda's response to COVID-19 was both systemic and opportunistic The Uganda’s anti-corruption architecture was strong in design but weak in practice and emergency conditions amplified enduring governance deficiencies. Conclusions: The study concludes that Uganda’s anti-corruption frameworks were ill-prepared structurally for crisis governance The study recommends a rethink of how best anti-corruption systems can be designed to function under stressful and emergency conditions like that of COVID19 Limitations: The study focused on Mbarara City, Mbarara District, and Rukungiri District. The districts may not be wholly representative of the whole country. The study also relied heavily on qualitative perceptions with interviews and focus groups dominating. Contributions: The study contributes to the literature by demonstrating that corruption in Uganda during COVID19 times was a predictable response of fragile institutions operating under the pressure during emergency, Keywords: corruption, Covid-19, governance, legal frameworks, Uganda